Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/mpr.1471
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the prevalence of any impairing childhood mental disorder in the national health interview survey

Abstract: This study investigates whether the 6-item Strengths and Difficulties Questionnaire SDQ (5 symptoms and one impact item) included in the National Health Interview Survey can be used to construct models that accurately estimate the prevalence of any impairing mental disorder among children 4–17 years old as measured by a shortened Child/Adolescent or Preschool Age Psychiatric Assessment (CAPA or PAPA). A subsample of 217 NHIS respondents completed a follow-up CAPA or PAPA interview. Logistic regression models w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…The SDQ measures have been shown to predict impairing mental health problems in children and adolescents, although the five‐item SDQ does not predict mental health problems as accurately as the original 25‐item scale, and SDQ measure has greater reliability for adolescents than for children (Ringeisen, Aldworth, Colpe, Pringle, & Simile, ). We also demonstrate the usefulness of the NHIS's mental health measures by comparing them with data on mental health treatment and medication use that are available in the 2005–2007 NHIS.…”
Section: Methodsmentioning
confidence: 99%
“…The SDQ measures have been shown to predict impairing mental health problems in children and adolescents, although the five‐item SDQ does not predict mental health problems as accurately as the original 25‐item scale, and SDQ measure has greater reliability for adolescents than for children (Ringeisen, Aldworth, Colpe, Pringle, & Simile, ). We also demonstrate the usefulness of the NHIS's mental health measures by comparing them with data on mental health treatment and medication use that are available in the 2005–2007 NHIS.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the recommendations of Ringeisen, Aldworth, Colpe, Pringle, and Simile (), a summary SDQ measure was created by summing items comprising the SDQ score and the impact item. This summary SDQ variable was utilized as the outcome variable in analyses as validation research has demonstrated that the SDQ score and impact item in tandem have further enhanced predictability of child's mental health status than when either measure is used alone (Ringeisen et al., ). Scores on the summary SDQ measure ranged from 0 to 13 (Cronbach's α = .67).…”
Section: Methodsmentioning
confidence: 99%
“…In binary response logistic regression, the slope parameters are the “estimands” of interest (e.g. Jacobi et al ., ; Ringeisen et al ., ), but there are four parameters of interest when Hill equation models are fit to observed data. These four parameters can be used to link an explanatory variable of interest with probability of a binary response.…”
Section: Introductionmentioning
confidence: 99%